Maritime Connectivity and Economic Inclusion: A Decade of Indonesia’s Sea Toll Program - Nasrullah, Muhammad Nur Cahyo Hidayat (Sinergi International Journal of Logistics, 2025)
Indonesia’s archipelagic geography poses significant logistical challenges, particularly in achieving equitable connectivity across its more than 17,000 islands. In response, the government launched the Sea Toll Program in 2014 to reduce logistics costs, address price disparities, and integrate remote regions into the national economy. This study aims to evaluate the performance of the Sea Toll Program, focusing on its impact on route expansion, infrastructure development, and commodity price stabilization. Employing a qualitative-descriptive methodology, the research utilizes secondary data from government agencies, international institutions, and academic sources. Comparative and thematic analyses are applied to assess logistics improvements and ongoing structural constraints. The results show substantial progress: route expansions from 3 to 39 between 2015 and 2024, port coverage increased to 109, and cargo volumes reached 24,556 TEUs. Notably, between 2018 and 2024, price reductions of 10–12% for essential commodities were recorded in remote regions, based on data from the Ministry of Trade and Central Bureau of Statistics (BPS). However, only 58.7% of ports are adequately equipped, and backhaul cargo utilization remains below 25%. Infrastructure gaps, fragmented digital systems, and limited intermodal integration continue to impede efficiency. The study concludes that while the Sea Toll Program has enhanced logistics connectivity and supported regional equity, systemic reforms are required to realize its full potential. These include infrastructure modernization, digital platform integration, intermodal coordination, and adaptive governance models. The findings offer a roadmap for future logistics strategies that support national resilience and inclusive development.